EKSPLOITASI WANITA DI MEDIA MASSA (PERSPEKTIF TEORI SOSIAL DAN KOMUNIKASI ISLAM) - Bahtar Bahtar (Hunafa: Jurnal Studia Islamika, 2006)
Woman exploitation in mass media both in electronic media and printing one is greatly influenced by point of view of  capitalist as the capital holder who accentuates his business interest. Ironically, this such a point of view is not concerned with the influence of information on the cognitive, affective aspects, and individual behavior as well as societal culture. In the mean time, Islam provides its adherents with freedom to perform their professions as long as they are in the rule of Islam communication ethics that is they perform their professions respectfully and ethically.Kata Kunci: Eksploitasi, wanita, media massa, teori sosial komunikasi Islam